2015
DOI: 10.1063/1.4919633
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity anomaly in a self-aggregating system: Triblock copolymer 17R4 in water

Abstract: The reverse Pluronic, triblock copolymer 17R4 is formed from poly(propylene oxide) (PPO) and poly(ethylene oxide) (PEO): PPO14 - PEO24 - PPO14, where the number of monomers in each block is denoted by the subscripts. In water, 17R4 has a micellization line marking the transition from a unimer network to self-aggregated spherical micelles which is quite near a cloud point curve above which the system separates into copolymer-rich and copolymer-poor liquid phases. The phase separation has an Ising-like, lower co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Consequently, the solution density excess, shown in the inset, monotonically decreased over the whole temperature range, showing no sign of saturation to a lower plateau value. Such different behavior was arguably related to the different association process of this poloxamer with a "reversed" structure, which progressively occurred over a broad temperature range extending up to the cloud point where liquid-liquid phase separation took place [52]. SANS measurements moreover confirmed that the 17R4 association into "flower" micelles was driven by a progressive dehydration process taking place over the temperature range 35 • C < T < 42 • C [44].…”
Section: Poloxamersmentioning
confidence: 90%
“…Consequently, the solution density excess, shown in the inset, monotonically decreased over the whole temperature range, showing no sign of saturation to a lower plateau value. Such different behavior was arguably related to the different association process of this poloxamer with a "reversed" structure, which progressively occurred over a broad temperature range extending up to the cloud point where liquid-liquid phase separation took place [52]. SANS measurements moreover confirmed that the 17R4 association into "flower" micelles was driven by a progressive dehydration process taking place over the temperature range 35 • C < T < 42 • C [44].…”
Section: Poloxamersmentioning
confidence: 90%